Change of CGRP Plasma Concentrations in Migraine after Discontinuation of CGRP-(Receptor) Monoclonal Antibodies - Bianca Raffaelli; Maria Terhart; Mira Pauline Fitzek; Kristin Sophie Lange; Jasper Mecklenburg; Lucas Hendrik Overeem; Anke Siebert; Elisabeth Storch; Uwe Reuter (MDPI AG, 2023)
Discontinuation of treatment with monoclonal antibodies (mAb) targeting the Calcitonin Gene-Related Peptide (CGRP) pathway leads to an increase in migraine frequency. We aimed to assess changes in free and total CGRP plasma concentrations after the discontinuation of CGRP(-receptor) mAbs. This prospective analysis included 59 patients with migraine (n = 25 erenumab, n = 25 galcanezumab, n = 9 fremanezumab) who discontinued mAbs after ≥8 months of treatment. Patients were visited at the time of the last mAb injection (V1) and 16 weeks later (V2). For control, 30 migraine patients without preventive drug therapy were included. We measured free CGRP plasma concentrations in the erenumab and fremanezumab group and total CGRP concentrations in the galcanezumab group. Free CGRP plasma concentrations did not change after treatment discontinuation [erenumab: V1 31.2 pg/mL (IQR 25.8-45.6), V2 30.3 pg/mL (IQR 22.9-47.6), p = 0.65; fremanezumab V1 29.4 pg/mL (IQR 16.4-61.9), V2 34.4 (19.2-62.0), p = 0.86]. Controls had similar CGRP values of 32.6 pg/mL (IQR 21.3-44.6). Total CGRP concentrations in the galcanezumab group were 5439.3 pg/mL (2412.7-6338.1) at V1, and decreased to 1853.2 pg/mL (1136.5-3297.0) at V2 (p < 0.001). Cessation of treatment with CGRP(-R) mAbs did not have an impact on the free-circulating CGRP concentrations. Total CGRP decreased significantly after three months of treatment discontinuation.